Effect of Cognitive and Central Auditory Impairments on Satisfaction of Amplification in Hearing Impaired Older Adults - Younes Lotfi; Hosein Talebi; Saeideh Mehr Kian; Mohammad Reza Khodaei; Soghrat Faghih Zadeh (University of Social Welfare & Rehabilitation Sciences, 2012)
Objectives: Older adults show many difficulties of speech perception in noisy situations due to peripheral and central auditory impairments, and cognitive dysfunctions. One of the most common rehabilitative procedures for older adults with hearing loss is amplification. However, there is some evidence of dissatisfaction of amplification in older adults. Methods & Materials: We assessed cognitive station, central auditory function, and satisfaction of 19 participants with hearing aids using mini-mental state examination (MMSE), dichotic digits test (DDT), and the satisfaction with amplification in daily life scale respectively. Our cases had moderate sensory hearing loss in both ears. Results: Kruskal-Wallis statistics showed significant correlation between cognitive impairments (MMSE scores) and satisfaction of amplification (P<0.05). In contrast, there was not significant correlation between DDT and satisfaction of amplification (P>0.05). Conclusion: We showed central auditory processing impairments in hearing impaired older adults with cognitive dysfunctions. It is indicated that older adults with hearing loss might have cognitive impairments inducing dissatisfaction of amplification.